2015
DOI: 10.1136/bmjopen-2015-008531
|View full text |Cite
|
Sign up to set email alerts
|

Metformin initiation and renal impairment: a cohort study in Denmark and the UK

Abstract: ObjectivesTo estimate prevalence of renal impairment, rate of decline in kidney function and changes in metformin use after decline in kidney function, in metformin initiators.Design, setting and participantsWe conducted this 2-country cohort study using routine data from northern Denmark and the UK during 2000–2011. We included metformin initiators among patients aged ≥30 years with medically treated diabetes.Main outcome measuresWe described patients’ demographics, comorbidity, co-medications and their estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
2
10
0
2
Order By: Relevance
“…The source population comprised residents captured by the Aarhus University Prescription Database (AUPD) in Denmark and the Clinical Practice Research Datalink (CPRD) in the UK. Both resources have been described elsewhere . The study population consisted of people with diabetes with ≥ 1 prescription(s) for glucose‐lowering agents in the AUPD or the CPRD during 2000–2011, aged ≥ 30 years at cohort entry (date of first glucose‐lowering prescription during the study period).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The source population comprised residents captured by the Aarhus University Prescription Database (AUPD) in Denmark and the Clinical Practice Research Datalink (CPRD) in the UK. Both resources have been described elsewhere . The study population consisted of people with diabetes with ≥ 1 prescription(s) for glucose‐lowering agents in the AUPD or the CPRD during 2000–2011, aged ≥ 30 years at cohort entry (date of first glucose‐lowering prescription during the study period).…”
Section: Methodsmentioning
confidence: 99%
“…the UK. Both resources have been described elsewhere [9]. The study population consisted of people with diabetes with ≥ 1 prescription(s) for glucose-lowering agents in the AUPD or the CPRD during 2000-2011, aged ≥ 30 years at cohort entry (date of first glucose-lowering prescription during the study period).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, other authors have put forward the case for metformin to be continued with lower levels of renal function and there is some evidence that this reflects current clinical practice. [80][81][82][83] In our experience, many prescribers adopt a pragmatic approach…”
Section: Discussionmentioning
confidence: 99%
“…Some physicians prefer to prescribe metformin 250 mg/d to peritoneal dialysis, and 500 mg/d after each dialysis to hemodialysis patients (26). While some of the physicians in their clinical practice do not prescribe if eGFR of patient is below 30 mL/min (27). A large prospective cohort study on patients with diabetes and CKD stage 4 showed that treatment with low-dose metformin during one month revealed stable pharmacokinetics and was not associated with adverse effects (28).…”
Section: Metformin Use In Early Ckd Stagesmentioning
confidence: 99%